2015
DOI: 10.1080/09593330.2015.1051135
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lead and phosphate ions from aqueous solutions by organo-smectite

Abstract: Smectite has been modified using hexadecyltrimethyl ammonium bromide in an amount of double cationic exchange capacity. This alteration makes it possible to use organo-smectite as a sorbent to remove anionic forms. The experiment consisted of the interchangeable sorption of phosphate(V) and lead(II) by organo-smectite. Research was carried out with varying pH (2-5) and various concentrations (0.1-5 mmol/L). Organo-smectite with previously adsorbed lead ions removed more phosphate than the untreated organo-smec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The preparation of the final sample consisted of several stages. First, the clay-size fraction (<2 μm) was separated from bentonite by a sedimentation process [25]. XRD confirmed that the only phase occurring after the separation procedure was Ca-montmorillonite and that all impurities from the initial sediment had been removed [12].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the final sample consisted of several stages. First, the clay-size fraction (<2 μm) was separated from bentonite by a sedimentation process [25]. XRD confirmed that the only phase occurring after the separation procedure was Ca-montmorillonite and that all impurities from the initial sediment had been removed [12].…”
Section: Methodsmentioning
confidence: 99%
“…The results of this work provide novel information for developing new effective adsorbents of heavy metals. Smectite was modified using hexadecyltrimethylammonium bromide which an amount to double cationic exchange capacity for the interchangeable sorption of phosphate (V) and Pb (II) (Bajda et al, 2015). Possible use of montmorillonite modified with polyethyleneimine was investigated by Goncharuk et al (2010) for the removal of Co (II) and Ni (II) metal ions from aqueous solutions.…”
Section: Modification With Organic Compoundsmentioning
confidence: 99%
“…Adsorption seems to be one of the best-suited methods, due to its high efficiency, low-cost, and ease of operation. Various adsorbents, such as carbon foam [30], activated carbon [31], zeolite [32], clay minerals [33,34], organic polymers [35], and biochar [36], and many waste materials, such as fly ash [37], reused sanding wastes [38], biomass [39], and water treatment residuals (WTRs) [40,41], have been used for the removal of heavy metals by adsorption. The most effective heavy metal adsorbents, especially for arsenic, are adsorbents based on metal oxides (Fe, Al, Mn oxides), such as WTRs, bog iron ores [42], ferrihydrite [43], goethite [44], layered double hydroxide (LDH) [45], Sn/Ti-Mn binary metal oxides [46,47], Al/Fe oxide-oxyhydroxide composite powders [48], and red mud [49].…”
Section: Introductionmentioning
confidence: 99%